BiP Heterozigosity Aggravates Pathological Deterioration in Experimental Amyotrophic Lateral Sclerosis - Marta Gómez-Almería (MDPI AG, 2021)
In the present study, we investigated the involvement of the chaperone protein BiP (also known as GRP78 or Hspa5), a master regulator of intracellular proteostasis, in two mouse models of neurodegenerative diseases: amyotrophic lateral sclerosis (ALS) and Parkinson’s disease (PD). To this end, we used mice bearing partial genetic deletion of the BiP gene (BiP+/− mice), which, for the ALS model, were crossed with mutant SOD1 (mSOD1) transgenic mice to generate mSOD1/BiP+/− double mutant mice. Our data revealed a more intense neurological decline in the double mutants, reflected in a greater deterioration of the neurological score and rotarod performance, with also a reduced animal survival, compared to mSOD1 transgenic mice. Such worsening was associated with higher microglial (labelled with Iba-1 immunostaining) and, to a lesser extent, astroglial (labelled with GFAP immunostaining) immunoreactivities found in the double mutants, but not with a higher loss of spinal motor neurons (labelled with Nissl staining) in the spinal cord. The morphological analysis of Iba-1 and GFAP-positive cells revealed a higher presence of activated cells, characterized by elevated cell body size and shorter processes, in double mutants compared to mSOD1 mice with normal BiP expression. In the case of the PD model, BiP+/− mice were unilaterally lesioned with the parkinsonian neurotoxin 6-hydroxydopamine (6-OHDA). In this case, however, we did not detect a greater susceptibility to damage in mutant mice, as the motor defects caused by 6-OHDA in the pole test and the cylinder rearing test, as well as the losses in tyrosine hydroxylase-containing neurons and the elevated glial reactivity (labelled with CD68 and GFAP immunostaining) detected in the substantia nigra were of similar magnitude in BiP+/− mice compared with wildtype animals. Therefore, our findings support the view that a dysregulation of the protein BiP may contribute to ALS pathogenesis. As BiP has been recently related to cannabinoid type-1 (CB1) receptor function, our work also opens the door to future studies on a possible link between BiP and the neuroprotective effects of cannabinoids that have been widely reported in this neuropathological context. In support of this possibility, preliminary data indicate that CB1 receptor levels are significantly reduced in mSOD1 mice having partial deletion of BiP gene.